The amount of coir composition effect on the flexural and tensile strength of coir composites - Arsyad, Muhammad; Kondo, Yan; Ridwan, Ridwan (Jurnal Polimesin, 2024)
This article is the result of research on the effect of soaking coir in sodium hydroxide solution. The objective of this study is to determine the effect of the composition of coir on the flexural and tensile strength of the coir composite as an effect of immersion in a sodium hydroxide (NaOH) solution. The stages of conducting the research are: (1) preparation of materials and tools; (2) treatment of coir and manufacture of composites; (3) tensile and flexural testing. Before being used as a composite reinforcement, coir was soaked in sodium hydroxide solution with a concentration (percent by weight) of 5% and 10% for 3 hours at room temperature 25oC. After that, the coir was washed with distilled water and then dried at room temperature for 18 hours. Next, we dried the coir in an oven at 90oC for 5 hours. After soaking, coir was used as a composite reinforcement with a composition of 10%, 15%, and 20% by weight of coir. The composite was made using the hand lay-up method, while the flexural test specimens were made based on ASTM-D790, and the tensile test was based on ASTM D 638-03. Then the flexural strength test of the coir composite was carried out using the Shimadzu Flexure Tester with a capacity of 5 kN and a compressive speed of 2 mm/minute. It was concluded that the highest flexural and tensile strengths were obtained by immersing coir in a 5% NaOH solution with 20% coir composition, respectively 41.114 MPa and 20.265 MPa.